Analysis of the Effectiveness and Efficiency of the Implementation of the Village Fund Budget in Semarang Regency - Nikmatuniayah; Lardin Korawijayanti; Siti Arbainah; Rikawati; Muhammad Rois (Admisi dan Bisnis, 2026)
To improve the quality and welfare of villages, the government has issued Village Funds, which can be used to build village infrastructure and facilities. The use of these Village Funds must be accounted for in financial reports. This study aims to identify the effectiveness and efficiency of Village Fund expenditure in Semarang Regency, using a case study of Mluweh and Kalikayen Villages, East Ungaran District, Semarang Regency, for the 2022-2024 budget period. The analytical methods used were descriptive analysis and data analysis to measure effectiveness and efficiency. The results of this study indicate that from 2022 to 2024, both Mluweh and Kalikayen villages demonstrated balanced effectiveness. Furthermore, from 2022 to 2024, both Mluweh and Kalikayen villages demonstrated efficiency. This means that the village government has been able to reduce expenditure while maintaining the implementation of village programs and activities.